5.19.6 Problems 501 to 600

Table 5.903: Third and higher order non-homogeneous ODE

#

ODE

Mathematica

Maple

17054

\[ {}y^{\prime \prime \prime }-y^{\prime \prime } = 1+{\mathrm e}^{x} \]

17055

\[ {}y^{\prime \prime \prime }+4 y^{\prime } = {\mathrm e}^{2 x}+\sin \left (2 x \right ) \]

17065

\[ {}y^{\prime \prime \prime \prime }+2 y^{\prime \prime \prime }+2 y^{\prime \prime }+2 y^{\prime }+y = x \,{\mathrm e}^{x}+\frac {\cos \left (x \right )}{2} \]

17067

\[ {}y^{\prime \prime \prime \prime }+4 y^{\prime \prime \prime } = {\mathrm e}^{x}+3 \sin \left (2 x \right )+1 \]

17083

\[ {}y^{\prime \prime \prime }-2 y^{\prime \prime }+y^{\prime } = {\mathrm e}^{x}+2 x \]

17085

\[ {}y^{\prime \prime \prime }-y^{\prime \prime }-2 y^{\prime } = 4 x +3 \sin \left (x \right )+\cos \left (x \right ) \]

17086

\[ {}y^{\prime \prime \prime }-4 y^{\prime } = {\mathrm e}^{2 x} x +\sin \left (x \right )+x^{2} \]

17087

\[ {}y^{\left (5\right )}-y^{\prime \prime \prime \prime } = x \,{\mathrm e}^{x}-1 \]

17088

\[ {}y^{\left (5\right )}-y^{\prime \prime \prime } = x +2 \,{\mathrm e}^{-x} \]

17103

\[ {}y^{\prime \prime \prime }-y^{\prime } = -2 x \]

17104

\[ {}y^{\prime \prime \prime \prime }-y = 8 \,{\mathrm e}^{x} \]

17105

\[ {}y^{\prime \prime \prime }-y = 2 x \]

17106

\[ {}y^{\prime \prime \prime \prime }-y = 8 \,{\mathrm e}^{x} \]

17156

\[ {}y^{\prime \prime \prime }+y^{\prime \prime } = \frac {x -1}{x^{3}} \]

17721

\[ {}y^{\prime \prime \prime \prime }-6 y = t \,{\mathrm e}^{-t} \]

17760

\[ {}y^{\prime \prime \prime \prime }-y = \operatorname {Heaviside}\left (t -1\right )-\operatorname {Heaviside}\left (t -2\right ) \]

17761

\[ {}y^{\prime \prime \prime \prime }+5 y^{\prime \prime }+4 y = 1-\operatorname {Heaviside}\left (t -\pi \right ) \]

17776

\[ {}y^{\prime \prime \prime \prime }-y = \delta \left (t -1\right ) \]

17788

\[ {}y^{\prime \prime \prime \prime }-16 y = g \left (t \right ) \]

17789

\[ {}y^{\prime \prime \prime \prime }+y^{\prime \prime }+16 y = g \left (t \right ) \]

17794

\[ {}y^{\prime \prime \prime \prime }+6 y^{\prime \prime \prime }+3 y = t \]

17795

\[ {}t y^{\prime \prime \prime }+\sin \left (t \right ) y^{\prime \prime }+8 y = \cos \left (t \right ) \]

17797

\[ {}y^{\prime \prime \prime }+t y^{\prime \prime }+t^{2} y^{\prime }+t^{2} y = \ln \left (t \right ) \]

17801

\[ {}t y^{\prime \prime \prime }+\sin \left (t \right ) y^{\prime \prime }+4 y = \cos \left (t \right ) \]

17803

\[ {}y^{\prime \prime \prime }+t y^{\prime \prime }+5 t^{2} y^{\prime }+2 t^{3} y = \ln \left (t \right ) \]

17970

\[ {}{y^{\prime \prime \prime }}^{2}+x^{2} = 1 \]

18003

\[ {}\left (x^{2}+2\right ) y^{\prime \prime \prime }-2 x y^{\prime \prime }+\left (x^{2}+2\right ) y^{\prime }-2 x y = x^{4}+12 \]

18018

\[ {}y^{\prime \prime \prime }+y^{\prime \prime }+y^{\prime }+y = x \,{\mathrm e}^{x} \]

18019

\[ {}y^{\prime \prime \prime \prime }-4 y^{\prime \prime \prime }+6 y^{\prime \prime }-4 y^{\prime }+y = \left (1+x \right ) {\mathrm e}^{x} \]

18030

\[ {}x^{3} y^{\prime \prime \prime }-x^{2} y^{\prime \prime }+2 x y^{\prime }-2 y = x^{3}+3 x \]

18373

\[ {}y^{\prime \prime \prime \prime } = \sin \left (x \right )+24 \]

18374

\[ {}y^{\prime \prime \prime }-3 y^{\prime \prime }+2 y^{\prime } = 10+42 \,{\mathrm e}^{3 x} \]

18375

\[ {}y^{\prime \prime \prime }-y^{\prime } = 1 \]

18387

\[ {}y^{\prime \prime \prime }-2 y^{\prime }+y = 2 x^{3}-3 x^{2}+4 x +5 \]

18389

\[ {}y^{\left (5\right )}-y^{\prime \prime \prime } = x^{2} \]

18390

\[ {}y^{\left (6\right )}-y = x^{10} \]

18393

\[ {}y^{\prime \prime \prime }-y^{\prime \prime } = 12 x -2 \]

18394

\[ {}y^{\prime \prime \prime }+y^{\prime \prime } = 9 x^{2}-2 x +1 \]

18398

\[ {}y^{\prime \prime \prime }-8 y = 16 x^{2} \]

18399

\[ {}y^{\prime \prime \prime \prime }-y = -x^{3}+1 \]

18400

\[ {}y^{\prime \prime \prime }-\frac {y^{\prime }}{4} = x \]

18401

\[ {}y^{\prime \prime \prime \prime } = \frac {1}{x^{3}} \]

18402

\[ {}y^{\prime \prime \prime }-y^{\prime \prime }+y^{\prime } = 1+x \]

18403

\[ {}y^{\prime \prime \prime }+2 y^{\prime \prime } = x \]

18404

\[ {}y^{\prime \prime \prime }-6 y^{\prime \prime }+12 y^{\prime }-8 y = {\mathrm e}^{2 x} \]

18405

\[ {}y^{\prime \prime \prime }+3 y^{\prime \prime }+3 y^{\prime }+y = 12 \,{\mathrm e}^{-x} \]

18589

\[ {}x^{\prime \prime \prime \prime }-6 x^{\prime \prime \prime }+11 x^{\prime \prime }-6 x^{\prime } = {\mathrm e}^{-3 t} \]

18590

\[ {}x^{4} y^{\prime \prime \prime \prime }+x^{3} y^{\prime \prime \prime }-20 x^{2} y^{\prime \prime }+20 x y^{\prime } = 17 x^{6} \]

18591

\[ {}t^{4} x^{\prime \prime \prime \prime }-2 t^{3} x^{\prime \prime \prime }-20 t^{2} x^{\prime \prime }+12 t x^{\prime }+16 x = \cos \left (3 \ln \left (t \right )\right ) \]

18593

\[ {}y^{\prime \prime \prime \prime }-3 y^{\prime \prime \prime }+3 y^{\prime \prime }-y^{\prime } = {\mathrm e}^{2 x} \]

18594

\[ {}y^{\prime \prime \prime }-y^{\prime \prime }+y^{\prime }-y = \cos \left (x \right ) \]

18665

\[ {}y^{\prime \prime \prime }+4 y^{\prime \prime }+3 y^{\prime } = x^{2} \]

18668

\[ {}y^{\prime \prime \prime }+5 y^{\prime \prime }+6 y^{\prime } = x \]

18669

\[ {}y^{\prime \prime \prime }-6 y^{\prime \prime }+11 y^{\prime }-6 y = x \]

18673

\[ {}y^{\prime \prime \prime }+y^{\prime \prime }-4 y^{\prime }-4 y = x \]

18675

\[ {}y^{\prime \prime \prime }-y^{\prime \prime }+y^{\prime }-y = \cos \left (x \right ) \]

18676

\[ {}y^{\prime \prime \prime }-3 y^{\prime \prime }+3 y^{\prime }-y = {\mathrm e}^{x} \]

18677

\[ {}y^{\prime \prime \prime \prime }-y = x^{4} \]

18684

\[ {}x^{3} y^{\prime \prime \prime }+7 x^{2} y^{\prime \prime }+8 x y^{\prime } = \ln \left (x \right )^{2} \]

18686

\[ {}x^{3} y^{\prime \prime \prime }-3 x^{2} y^{\prime \prime }+6 x y^{\prime }-6 y = x^{3} \]

18687

\[ {}x^{3} y^{\prime \prime \prime }+2 x^{2} y^{\prime \prime }-4 x y^{\prime }+4 y = \ln \left (x \right ) \]

18696

\[ {}\left (x^{3}+x^{2}-3 x +1\right ) y^{\prime \prime \prime }+\left (9 x^{2}+6 x -9\right ) y^{\prime \prime }+\left (18 x +6\right ) y^{\prime }+6 y = x^{3} \]

18697

\[ {}x^{2} y^{\prime \prime \prime }+5 x y^{\prime \prime }+4 y^{\prime } = -\frac {1}{x^{2}} \]

18879

\[ {}y^{\prime \prime \prime }-y^{\prime \prime }-8 y^{\prime }+12 y = X \left (x \right ) \]

18880

\[ {}y^{\prime \prime \prime }+y = 3+{\mathrm e}^{-x}+5 \,{\mathrm e}^{2 x} \]

18881

\[ {}y^{\prime \prime \prime }-y = \left (1+{\mathrm e}^{x}\right )^{2} \]

18883

\[ {}y^{\prime \prime \prime }+3 y^{\prime \prime }+2 y^{\prime } = x^{2} \]

18884

\[ {}y^{\prime \prime \prime }+8 y = x^{4}+2 x +1 \]

18885

\[ {}y^{\prime \prime \prime }+y^{\prime \prime }-y^{\prime }-y = \cos \left (2 x \right ) \]

18888

\[ {}y^{\prime \prime \prime }+y = \sin \left (3 x \right )-\cos \left (\frac {x}{2}\right )^{2} \]

18889

\[ {}y^{\prime \prime \prime \prime }+y = {\mathrm e}^{2 x} x \]

18896

\[ {}y^{\prime \prime \prime }+2 y^{\prime \prime }+y^{\prime } = {\mathrm e}^{2 x}+x^{2}+x \]

18900

\[ {}y^{\prime \prime \prime }-3 y^{\prime \prime }-6 y^{\prime }+8 y = x \]

18901

\[ {}y^{\prime \prime \prime \prime }+y^{\prime \prime \prime }+y^{\prime \prime } = x^{2} \left (b x +a \right ) \]

18902

\[ {}y^{\prime \prime \prime }-13 y^{\prime }+12 y = x \]

18903

\[ {}y^{\prime \prime \prime \prime }+2 n^{2} y^{\prime \prime }+n^{4} y = \cos \left (m x \right ) \]

18904

\[ {}y^{\prime \prime \prime \prime }+2 y^{\prime \prime }+y = x^{2} \cos \left (x \right ) \]

18908

\[ {}y^{\prime \prime \prime \prime }-a^{4} y = x^{4} \]

18909

\[ {}y^{\prime \prime \prime \prime }-2 y^{\prime \prime \prime }+y^{\prime \prime } = x \]

18910

\[ {}y^{\prime \prime \prime \prime }-y = {\mathrm e}^{x} \cos \left (x \right ) \]

18912

\[ {}y^{\prime \prime \prime }-7 y^{\prime }-6 y = {\mathrm e}^{2 x} \left (1+x \right ) \]

18914

\[ {}y^{\prime \prime \prime }+3 y^{\prime \prime }+3 y^{\prime }+y = {\mathrm e}^{-x} \]

18915

\[ {}y^{\prime \prime \prime \prime }-2 y^{\prime \prime \prime }-3 y^{\prime \prime }+4 y^{\prime }+4 y = {\mathrm e}^{x} x^{2} \]

18916

\[ {}y^{\prime \prime \prime }-3 y^{\prime \prime }+3 y^{\prime }-y = x \,{\mathrm e}^{x}+{\mathrm e}^{x} \]

18919

\[ {}y^{\prime \prime \prime }-3 y^{\prime \prime }+4 y^{\prime }-2 y = {\mathrm e}^{x}+\cos \left (x \right ) \]

18921

\[ {}y^{\prime \prime \prime }-3 y^{\prime \prime }+4 y = {\mathrm e}^{3 x} \]

18922

\[ {}y^{\prime \prime \prime }+y = \sin \left (x \right ) {\mathrm e}^{2 x}+{\mathrm e}^{\frac {x}{2}} \sin \left (\frac {\sqrt {3}\, x}{2}\right ) \]

18933

\[ {}y^{\prime \prime \prime }-\frac {4 y^{\prime \prime }}{x}+\frac {5 y^{\prime }}{x^{2}}-\frac {2 y}{x^{3}} = 1 \]

18938

\[ {}x^{3} y^{\prime \prime \prime }+2 x^{2} y^{\prime \prime }+2 y = 10 c +\frac {10}{x} \]

18939

\[ {}16 \left (1+x \right )^{4} y^{\prime \prime \prime \prime }+96 \left (1+x \right )^{3} y^{\prime \prime \prime }+104 \left (1+x \right )^{2} y^{\prime \prime }+8 \left (1+x \right ) y^{\prime }+y = x^{2}+4 x +3 \]

18942

\[ {}x^{4} y^{\prime \prime \prime \prime }+6 x^{3} y^{\prime \prime \prime }+9 x^{2} y^{\prime \prime }+3 x y^{\prime }+y = \left (\ln \left (x \right )+1\right )^{2} \]

18943

\[ {}x^{4} y^{\prime \prime \prime }+2 x^{3} y^{\prime \prime }-x^{2} y^{\prime }+x y = 1 \]

18954

\[ {}y^{\prime \prime \prime } = x \,{\mathrm e}^{x} \]

18955

\[ {}x^{2} y^{\prime \prime \prime \prime }+1 = 0 \]

18961

\[ {}x^{2} y^{\prime \prime \prime }-4 x y^{\prime \prime }+6 y^{\prime } = 4 \]

18964

\[ {}2 x y^{\prime \prime \prime } y^{\prime \prime } = {y^{\prime \prime }}^{2}-a^{2} \]

18970

\[ {}y^{\left (5\right )}-m^{2} y^{\prime \prime \prime } = {\mathrm e}^{a x} \]

18975

\[ {}y^{\prime \prime \prime } y^{\prime \prime } = 2 \]

18985

\[ {}x^{3} y^{\prime \prime \prime }+4 x^{2} y^{\prime \prime }+x \left (x^{2}+2\right ) y^{\prime }+3 x^{2} y = 2 x \]

18988

\[ {}\left (x^{3}-x \right ) y^{\prime \prime \prime }+\left (8 x^{2}-3\right ) y^{\prime \prime }+14 x y^{\prime }+4 y = \frac {2}{x^{3}} \]